Understanding Communication Barriers of New Members on Milis Sehat - Annisa Zetta Afiatni; Dra Taufik Spurihartini; Turnomo Rahardjo .; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Nowadays, people can take health discussion in cyberspace, Milis Sehat is one that provides a forum for the public. You can consulted directly with doctors without going through face-to-face. The existence of a new way of discussion or consultation about the health from became online that creates barriers in each members. Therefore, researcher interested to discuss what are the barriers that prevent members on Milis Sehat and how they achieve a common understanding when communicating effort. The purpose of this study is to describe the factors inhibiting new members on Milis Sehat when they are not able to reach a mutual understanding and to describe their efforts in reaching a mutual understanding. The theory that used is Accommodation Communication Theory (Howard Giles).This study uses an interpretive paradigm with a phenomenological approach of Moustakas. The results from this study is there are six barriers perceived by new members. The most dominant barriers is a psychological barrier in the form of their feeling less satisfied with the answers or the results of discussions on the mailing list because the answer just a link that contains articles; their discomfort when communicating because doctors in mailing lists according to their fierce; and their anxiety for fear the question is not got a response by anyone. Semantic barriers they experienced as a result of the use of the abbreviation / term health unfamiliar and less familiar to them. To understand this, they look for abbreviations / that term in the search engine Google, asking senior members or doctors in the mailing list. Frame of mind and cultural differences are also preventing them interpret what they read the writing on the mailing list. Barriers for their status within the social and technical barriers caused less supportive tool shared by several informants. In order to achieve mutual understanding, communication barriers have to be overcome first like a psychological barrier, status, culture, and mindset through mutual understanding their individual differences; semantic barriers can be overcome by finding yourself or ask about the language / vocabulary of what you do not understand, once they understand, they can converge (equalization) in order to make it look the same as the other members. Technical barriers can be overcome by using tools that support. Academically, Accommodation Communication Theory (Howard Giles) describes someone convergence for wanting approval. Meanwhile, someone from the findings converge to make it more practical and effective. In practical terms, the findings of this study can be applied to individuals who have a similar situation as in this study. Socially, the benefits that can be taken by the public should be when you are in this situation in order to look the same convergence with new people.